Dorobek prasoznawczy profesor Hanny Tadeusiewicz - Kristanova, Evelina (Acta Universitatis Lodziensis. Folia Librorum, 2010)
The author presents scientific works about Polish historical press of Hanna Tadeusiewicz. The professor wrote many articles about printing periodicals in XIX and XX century like “Czcionka”, “Praca”, “Drukarz i Księgarz” and unknown titles like “Chwila Spoczynku” or “Motyl”. There is the bibliography of works, too.